Between comings and goings, the house - José Antonio Santos de Oliveira (Universidade Estadual de Alagoas, 2023)
The present work, based on the Theory of the Imaginary, tries to find the imagery itinerary of José Luís Peixoto in the Return home, starting from the discussions about the myth of return - resonated since the Odyssey - and the Poetics of space, by Bachelard (2008), since these two images (return/home) are intertwined throughout the poetic narrative, which Added to these two founding elements of the text, it is observed how time in the closed space of the house unlocked, in the subject, feelings of fear and uncertainty in the face of the present. In this sense, it was found that the image of the house, in the aforementioned book, still recovers the symbolic of a protective space, updated in the experience of social isolation. The same update movement happens in the recovery of the Homeric myth, from which one can think of how the subjects found the need to return to the family environment because of the pandemic, at the same time that the For the realization of this article, we resort to the theoretical-methodological postulates of Bachelard (2008), Durand (1993), Mello (2002) and other authors.